Bringing People Together: Improving Intergroup Relations via Group Identity Cues. Issue 1 (January 2021) - Martinez-Ebers, Valerie; Calfano, Brian Robert; Branton, Regina
Many U.S. cities pursue a "human relations" strategy in response to racial and ethnic group conflict. Reflective of Common Ingroup Identity theory, human relations practitioners emphasize a superordinate community identity among residents from different groups for the purpose of "bringing people together" in an effort to improve intergroup relations. Practitioners also encourage intergroup contact to promote positive change in attitudes. Herein, we test the influence of group identity cues and intergroup contact as predictors of perceived intergroup commonality. The findings suggest emphasizing a superordinate community identity increases feelings of commonality in the attitudes of Anglos and Latinos toward one another and toward African-Americans and Asians, while intergroup contact has no significant influence on intergroup attitudes. These findings contribute to the extant literature by simultaneously testing the relative effect of salient group identities on intergroup attitudes and expanding the focus beyond the binary comparison found in most studies of racial–ethnic relations.